Hubungan Ansietas Terhadap Mekanisme Koping Praktek Klinik Mahasiswa Keperawatan STIKes Bani Saleh Pada Masa Pandemi Covid-19 - Syifa Rahmawati; Nur Miladiyah Rahmah; Yusrini Yusrini (JKM : Jurnal Keperawatan Merdeka, 2022)
Introduction: Clinical practice is mandatory for nursing students to achieve competency targets during lectures. Clinical practice during the COVID-19 pandemic is a new challenge for nursing students that can cause anxiety, and that can affect students' coping mechanisms during clinical practice. Objective: The purpose of the study was to determine the relationship between anxiety and coping mechanisms in nursing students who carried out clinical practice during the COVID-19 pandemic. Methods: This research design is a correlation study with a cross sectional design. The study population was 141 nursing students who carried out clinical practice during the COVID-19 pandemic, using the accidental sampling technique with a sample of 110 respondents. This study used the ZSAS questionnaire for anxiety and The Brief Cope questionnaire for coping mechanisms. Results: The results of the study students were not anxious (56.4%) and used adaptive coping mechanisms (51.8%). Bivariate analysis found that there was a relationship between anxiety and coping mechanisms. The result of p-value 0.039, p value <α(0.05). Conclusion: research shows that the majority of nursing students are not anxious and have adaptive coping mechanisms during clinical practice during the COVID-19 pandemic. Keywords: Anxiety; Covid-19; Clinical Practice; Coping Mechanism; Nursing Students